Fabrication and field emission properties of vertical, tapered GaN nanowires etched via phosphoric acid. (27th October 2021) - Kazanowska, Barbara A; Sapkota, Keshab R; Lu, Ping; Talin, A Alec; Bussmann, Ezra; Ohta, Taisuke; Gunning, Brendan P; Jones, Kevin S; Wang, George T
Abstract: The controlled fabrication of vertical, tapered, and high-aspect ratio GaN nanowires via a two-step top-down process consisting of an inductively coupled plasma reactive ion etch followed by a hot, 85% H3 PO4 crystallographic wet etch is explored. The vertical nanowires are oriented in the [ 0001 ] direction and are bound by sidewalls comprising of 33 6 ̄ 2 semipolar planes which are at a 12° angle from the [0001] axis. High temperature H3 PO4 etching between 60 °C and 95 °C result in smooth semipolar faceting with no visible micro-faceting, whereas a 50 °C etch reveals a micro-faceted etch evolution. High-angle annular dark-field scanning transmission electron microscopy imaging confirms nanowire tip dimensions down to 8–12 nanometers. The activation energy associated with the etch process is 0.90 ± 0.09 eV, which is consistent with a reaction-rate limited dissolution process. The exposure of the 33 6 ̄ 2 type planes is consistent with etching barrier index calculations. The field emission properties of the nanowires were investigated via a nanoprobe in a scanning electron microscope as well as by a vacuum field emission electron microscope. The measurements show a gap size dependent turn-on voltage, with a maximum current of 33 nA and turn-on field of 1.92 V nm −1 for a 50 nm gap, and uniform emission across the array.